2005
DOI: 10.1051/rnd:2005040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding live yeast products to calves with failure of passive transfer on performance and patterns of antibiotic resistance in fecalEscherichia coli

Abstract: -Fifty-two newborn Holstein calves with serum IgG concentrations less than 0.73 g·dL -1 were randomly assigned to one of four treatments: no added live yeast (control), 0.5 g of live yeast added to the grain for 84 d (SC; Saccharomyces cerevisiae), 0.5 g of live yeast added to the milk for 42 d (SB; S. cerevisiae, spp. boulardii), and 0.5 g of live yeast added to the grain for 84 d and to the milk for 42 d (SCSB). Calves were offered 440 g of milk replacer DM for the first 42 d and grain for ad libitum intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 22 publications
9
104
4
Order By: Relevance
“…Therefore these results suggest that the maturation of the microbial ecosystem is accelerated in the presence of the yeast. A recent study reports the effectiveness of using this yeast strain in young calves deprived of colostrum on grain intake and on growth performance, especially before weaning, with additional benefits on health status of the animals as number of days with diarrhea was significantly reduced in the ADY group (Galvao et al, 2005). This work illustrates well what impact of such a probiotic yeast, through its effect on establishment of microbial communities in the rumen, can have on animal performance and health.…”
Section: Impact Of Live Yeasts On Rumen Maturitymentioning
confidence: 68%
“…Therefore these results suggest that the maturation of the microbial ecosystem is accelerated in the presence of the yeast. A recent study reports the effectiveness of using this yeast strain in young calves deprived of colostrum on grain intake and on growth performance, especially before weaning, with additional benefits on health status of the animals as number of days with diarrhea was significantly reduced in the ADY group (Galvao et al, 2005). This work illustrates well what impact of such a probiotic yeast, through its effect on establishment of microbial communities in the rumen, can have on animal performance and health.…”
Section: Impact Of Live Yeasts On Rumen Maturitymentioning
confidence: 68%
“…Some studies reported that yeast cell wall components interact with immune systems, stimulating macrophage activation (Selijelid et al, 1987;Djeraba and Quere, 2000). Previous studies also reported that supplementation with 2% yeast culture improved fecal scores, reduced days with watery feces and reduced risk of health disorders in Holstein calves, and also that incorporating live yeast into the grain feed reduced the number of days the calves were afflicted with diarrhea (Galvã o et al, 2005;Magalhã es et al, 2008). Nevertheless, few studies on the efficacy of yeast or yeast products on health or immune activity in young calves are available (Seymour et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ingestion of S. cerevisiae improves milk production of cows and pig growth. 32,33) S. boulardii, which is genetically related to S. cerevisiae, is useful in treating antibiotic-associated diarrhea caused by Clostridium difficile. 34,35) Ingestion of -glucan derived from S. cerevisiae improves immune function and growth performance in livestock.…”
Section: Discussionmentioning
confidence: 99%